MEMBANGUN KODE GOLAY (24, 12, 8) DENGAN MATRTKS GENERATOR DAN MENGGUNAKAN KRITERIA PERMUTASI - Irawanto, Bambang; Rizki K., Ikhsan (JURNAL SAINS DAN MATEMATIKA, 2009)
ABSTRACT- -One of the more useful block codes k the binary Q4, .12, 8) etended Golay code.The binary (24, 12, 8) actended Golay code can be constructed through the direct sum operationwith irwolvetwo product codes. This methodform the generator matrixframework of the (24, 12, 8) Golay code that isbasedontheso-calledTuytnorla+xlb +xla+ b+xlcanstntction,wherea,bE Crandxe C', C,andC',is the (8, 4, 4) Iinear block codes. C, can be gotten through row permutation of the parity submaffix of CLWith q and C', and by applying the generator matrixframework of the (24. 12, S) Golry code get the binary(24, 12, 8) utended Golay code..Keyword :Block codes, direct sum, Goloy Code, product codes.